Pengaruh Metode Pembelajaran Terhadap Sikap Sosial Pada Mata Pelajaran Ips Di Sekolah Dasar (Studi Eksperiment Siswa Kelas V Di Sd Negeri 106 Karya Baru) - Ashari Usman (Prodi PGSD Unsultra, 2022)
This study aims to determine the influence and differences between the Role Playing method and the Varied Lecture method on the social attitudes of fifth-grade elementary school students in social studies learning. This research employed an experimental design. Based on the analysis and discussion, several findings were obtained: the social attitudes of elementary school students who learned through the Role Playing method were higher than those who learned through the Varied Lecture method. From these findings, it can be concluded that students who were taught using the Role Playing method demonstrated better social attitudes in social studies compared to those taught using the Varied Lecture method. Furthermore, students with high social attitudes benefited more from learning through Role Playing, while students with low social attitudes showed better results when taught using the Varied Lecture method.